Financial capability and functional financial literacy in young adults with developmental language disorder. (August 2018) - Winstanley, Maxine; Durkin, Kevin; Webb, Roger T; Conti-Ramsden, Gina
Background: Financial capability is an essential feature of the organisation of one's personal life and engagement with society. Very little is known of how adequately individuals with developmental language disorder handle financial matters. It is known that language difficulties place them at a disadvantage in many aspects of their development and during their transition into adulthood, leading to the possibility that financial issues may prove burdensome for them. This study examines the financial capability and functional financial literacy of young adults with developmental language disorder and compares them to those of age matched peers. We tested the expectation that those with developmental language disorder would find financial management more challenging than would their peers, and that they would need to seek greater support from family members or other people. Methods: Participants completed a detailed individual interview, which included items drawn from the British Household Panel Survey and additional measures of financial capability, functional financial literacy and of perceived support. Nonverbal IQ, language, reading and numeracy measures were also collected. Results: Compared to typically developing age matched peers, young people with developmental language disorder report less extensive engagement with financial products and lower competence in functional financial literacy. A considerably higher proportion of those with developmental language disorder (48% vs. 16% of age matched peers) report that they draw on support, primarily from parents, in various financial tasks, including paying bills, choosing financial products, and taking loans from family or friends. Conclusions: This is the first study to consider the financial capability skills and functional financial literacy of young adults with developmental language disorder. We provide novel evidence that some young adults with developmental language disorder lack functional financial skills and require support to successfully manage their finances. This has policy implications that relate not only to engaging affected individuals in discussions about financial management but also to wider familial support.